(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Bhandary MJ, Chandrashekar KR. 2014. Diversity and use of ethnomedicinal plants in coastal Karnataka, India. Biodiversitas 15: 8993. A study was undertaken in Coastal Karnataka, a culturally and floristically diverse region between the Western Ghats and the Arabian sea in India, to document the diversity and uses of ethnomedicinal plants of the area. This study resulted in the documentation of ethnomedicinal uses of 342 species of plants belonging to 34 families. The dominant families of ethnomedicinal plants were: Fabaceae (38 species), Euphorbiaceae (22 species), Rubiaceae (11 species), Acanthaceae, Asteraceae, Apocynaceae and Rutaceae (10 species each). Among the plants used, 30% are herbs, 27% trees, 25% climbers and 18% shrubs. Majority of the plants are used against several diseases, either alone or in combination with other plants. The most popular medicinal plants, in terms of the number of diseases against which they are used, are Cyclea peltata, Aristolochia indica, Cuminum cyminum, Curcuma longa, Tamarindus indica, Asparagus racemosus, Ficus racemosa, Hemidesmus indicus, Ficus religiosa, Calotropis gigantea, Vitex negundo, Aegle marmelos and Leucas aspera. A list of 50 important ethnomedicinal plants of the region which are used in the treatment of 5 or more disorders is provided.